Effect of Dietary Patterns on Muscle Strength and Physical Performance in the Very Old: Findings from the Newcastle 85+ Study. - Antoneta Granic; Carol Jagger; Karen Davies; Ashley Adamson; Thomas Kirkwood; Tom R Hill; Mario Siervo; John C Mathers; Avan Aihie Sayer (PLoS ONE)
Background Healthy diet has been associated with better muscle strength and physical performance in cross-sectional studies of older adults but the effect of dietary patterns (DP) on subsequent decline, particularly in the very old (aged 85+), has not been determined. Objective We investigated the association between previously established DP and decline in muscle strength and physical performance in the very old. Design 791 participants (61.8% women) from the Newcastle 85+ Study were followed-up for change in hand grip strength (HGS) and Timed Up-and Go (TUG) test over 5 years (four waves 1.5 years apart). Mixed models were used to determine the effects of DP on muscle strength and physical performance in the entire cohort and separately by sex. Results Previously we have established three DP that varied in intake of red meats, potato, gravy and butter and differed with key health and social factors. HGS declined linearly by 1.59 kgF in men and 1.08 kgF in women (both p<0.001), and TUG slowed by 0.13 log10-transformed seconds (log10-s) in men and 0.11 log10-s in women per wave after adjusting for important covariates (both p<0.001), and also showed a nonlinear change (p<0.001). Men in DP1 ('High Red Meat') had worse overall HGS (β = -1.70, p = 0.05), but men in DP3 ('High Butter') had a steeper decline (β = -0.63, p = 0.05) than men in DP2 ('Low Meat'). Men in DP1 and women in DP3 also had overall slower TUG than those in DP2 (β = 0.08, p = 0.001 and β = 0.06, p = 0.01, respectively), but similar rate of decline after adjusting for sociodemographic, lifestyle, health, and functioning factors. The results for HGS and TUG were not affected by participants' cognitive status. Conclusions DP high in red meats, potato and gravy (DP1), or butter (DP3) may adversely affect muscle strength and physical performance in later life, independently of important covariates and cognitive status.